EDUCATION METHODICAL BASES INDIVIDUAL SCHOLASTIC OF THE FUNCTIONING THE TEACHER PROFESSIONAL SCIENCES - Mullakhmetov, Radik; Kadirov, Xayot; Ruzieva, Nasiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This article is dedicated to the opinions about scientific methodical basis of individual educational upbringing works in the process of professional training teachers’ activities and recommendations on individual pedagogical technologies concerning to exact peculiarities of modern higher educational system working programs are given.